2013
DOI: 10.1111/fare.12036
|View full text |Cite
|
Sign up to set email alerts
|

Complexities of Informal Social Support Arrangements for Black Lesbian Couples

Abstract: This qualitative study examined how Black lesbian couples receive informal social support from their social networks. Guided by an integrated framework of symbolic interactionism and Black feminist theory, interviews were conducted with 11 Black lesbian couples (22 individuals) in committed relationships. Using grounded theory methodology, it was found that Black lesbian couples received informal social support from different sources, but that this support was provided to individuals as a means of sustaining i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 49 publications
1
43
1
Order By: Relevance
“…Fogg-Davis (2001) clarified this further, noting the distinction between genetic traits and ties and arguing that a choice to develop kinship networks outside of genetic ties does not mean a devaluing of those ties. Glass and Few-Demo's (2013) work with Black lesbian mothers highlights that in the context of oppressive race-based policies, kinship networks became central to survival and to the sharing of cultural rituals and practice, which suggests a focus on kinship relationships as an act of resistance rather than a choice to decentralize genetic relationships. Roberts (1997) described how White supremacy in the United States hinges on White control of Black women's reproduction, including through recent coercive permanent or semipermanent sterilization programs.…”
Section: Sociohistorical Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Fogg-Davis (2001) clarified this further, noting the distinction between genetic traits and ties and arguing that a choice to develop kinship networks outside of genetic ties does not mean a devaluing of those ties. Glass and Few-Demo's (2013) work with Black lesbian mothers highlights that in the context of oppressive race-based policies, kinship networks became central to survival and to the sharing of cultural rituals and practice, which suggests a focus on kinship relationships as an act of resistance rather than a choice to decentralize genetic relationships. Roberts (1997) described how White supremacy in the United States hinges on White control of Black women's reproduction, including through recent coercive permanent or semipermanent sterilization programs.…”
Section: Sociohistorical Contextmentioning
confidence: 99%
“…Researchers are beginning to examine experiences of lesbian families of color post conception (Glass & Few-Demo, 2013;Rostosky, Riggle, Savage, Roberts, & Singletary, 2008;Steinbugler, 2005). This research focuses largely on families' attempts to manage stigma and overall mental health and does not examine pathways to family formation in the context of social identity.…”
Section: Family Formation Among Lbq-identified Womenmentioning
confidence: 99%
“…Similarly, in a content analysis of open-ended responses from LGB adults, individuals reported that state-level antigay politics negatively affected their psychological well-being (Rostosky, Riggle, Horne, Denton, & Huellemeier, 2010). A study of Black lesbian couples found that pastors and congregants were alienating toward couples and their children, even as they expressed support for the lesbians as individuals (Glass & Few-Demo, 2013). As a result, the women felt alienated and that their families were not supported.…”
Section: Perceived Residential Community Climatementioning
confidence: 99%
“…This consideration of within‐group diversity is a theoretical feature crucial to future research on sexual minorities who are also a racial minority, and one that can aid in responding to scholars' call to understand intragroup variations among that population. Are Chiron's experiences as a Black LGBT person the same as, say, those of transgender actress Laverne Cox, also a “Black LGBT person?” Are they analogous to those of the Black lesbian couples in Glass and Few‐Demo's () study, one of the few variations of intersectionality applied to sexual minority samples in leading family journals (van Eeden‐Moorefield et al, )? Does Chiron's story parallel that of other gay Black men including TV personality RuPaul Andre Charles, journalist Don Lemon, and professional football player Michael Sam (the first openly gay athlete to be drafted by the National Football League)?…”
Section: Moonlight In An Intersectional Frameworkmentioning
confidence: 98%